PERAN GURU PENDIDIKAN AGAMA ISLAM SEBAGAI PENDIDIK DALAM PEMBENTUKAN KARAKTER BERBASIS POTENSI DIRI KELAS VIII DI SMP MA’ARIF GENTENG - Imam Mashuri; Al Muftiyah; Fitra Dewi Nur Azizah (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
The task of educating is responsible for all the development of students, up to the maturity of students. So in this case the teacher as an educator also plays a role in shaping the character of students based on the potential of each individual. This study generally aims to describe the role of Islamic Religious Education Teachers as Educators in Character Building Based on Self-Potentials for Class VIII SMP Ma'arif Genteng for the 2020/2021 Academic Year, as well as to determine the supporting and inhibiting factors. This study uses a descriptive qualitative approach, then the data sources in this study came from the results of interviews with the Principal, Islamic Religious Education Teachers, and Students of Ma'arif Genteng Middle School for the 2020/2021 Academic Year which were determined through purposive sampling. And in a ready-made form of publication. The method of collecting is by using interviews, observation and documentation. While the data analysis using Miles and Huberman, namely by reducing the data, presenting the data and drawing conclusions. and researchers tested the validity of the data using source triangulation techniques. Based on the results of interviews and observations that have been carried out by researchers, it is found data stating that the role of Islamic Religious Education Teachers as Educators which includes as teachers, motivators and evaluators has been carried out in a way that is adapted to students. In addition, it was also found that there is a process of character building based on self-potential which includes mind mapping, multiple intelligence, and effective thinking in students with a stimulus and through the stages of moral knowing, moral feeling and moral action. These findings prove that Islamic Religious Education Teachers have carried out their roles well although not yet one hundred percent, and students have been able to bring up their potential for mind mapping, multiple intelligence, and effective thinking, which still need to be honed and forged again in order to become better useful for yourself and others.